2020
DOI: 10.1021/acsami.0c12642
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive and Stretchable Strain Sensor Based on a Synergistic Hybrid Conductive Network

Abstract: Highly sensitive and stretchable strain sensors have attracted considerable attention due to their promising applications in human motion detection, soft robot, wearable electronics, etc. However, there is still a trade-off between high sensitivity and high stretchability. Here, we reported a stretchable strain sensor by sandwiching reduced graphene oxide (RGO)-coated polystyrene microspheres (PS@RGO) and silver nanowires (AgNWs) conductive hybrids in an elastic polydimethylsiloxane (PDMS) matrix. Due to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 45 publications
0
42
0
Order By: Relevance
“…A type of effective approach is to use the nanocomposite materials to form the conductive mesh structure to maintain electrical conduction paths in the elastic composite at large strain. [ 15,25,45–59 ] Huang et al used the CNT network as the mesh structure, which bridged dispersed silver nanoparticles (AgNPs) in thermoplastic polyurethane electrospun membrane (TPUEM) ( Figure a). [ 45 ] Compared with the sensor device without CNTs, the stretchability of the sensor was improved to 550%, and a high GF of 7066 at 500% strain was achieved (Figure 3b).…”
Section: Device Designmentioning
confidence: 99%
See 1 more Smart Citation
“…A type of effective approach is to use the nanocomposite materials to form the conductive mesh structure to maintain electrical conduction paths in the elastic composite at large strain. [ 15,25,45–59 ] Huang et al used the CNT network as the mesh structure, which bridged dispersed silver nanoparticles (AgNPs) in thermoplastic polyurethane electrospun membrane (TPUEM) ( Figure a). [ 45 ] Compared with the sensor device without CNTs, the stretchability of the sensor was improved to 550%, and a high GF of 7066 at 500% strain was achieved (Figure 3b).…”
Section: Device Designmentioning
confidence: 99%
“…Similarly, Liu et al reported a stretchable strain sensor by sandwiching reduced graphene oxide (RGO)‐coated polystyrene microspheres (PS@RGO) and silver nanowires (AgNWs) in an elastic polydimethylsiloxane (PDMS) matrix. [ 46 ] High‐aspect‐ratio AgNWs were used to connect the adjacent PS@RGO microspheres to prevent the electrical failure of the sensor at large strain. By adjusting the AgNW concentration, the sensor exhibited capability of measuring a wide range strain up to 230% with a large GF of 11 at 0−60% of strain and 47 at 100−230% of strain.…”
Section: Device Designmentioning
confidence: 99%
“…To solve the above limitations, it is essential to construct novel mechanically stretchable and multifunctional conductive networks on breathable substrates. Although conducting polymers, , metal particles, , and carbon-based materials such as CNTs and graphene , have been successfully developed in recent years, the serious aggregation of metal particles, the low electrical conductivity and environmental instability of conducting polymers, and the high contact resistance between carbon-based materials lead to performances that are far from what is expected. Furthermore, the assembly of microscopic conductive units such as nanoparticles, nanotubes, and nanosheets into high-performance interconnected macroscopic conductive networks is still challenging due to the weak interfacial contacts between the units, which seriously decrease the stretchability and sensitivity of wearable electronics.…”
Section: Introductionmentioning
confidence: 99%
“…Conductive carbon materials and metal llers are oen used together to reinforce the electrical conductivity or mechanical properties of the composites by simple mixing 31,32 or mutual modication. [33][34][35] When this hybrid ller is used to fabricate lled conductive composites, it shows good dispersibility in the matrix.…”
Section: Introductionmentioning
confidence: 99%